Population genetics of sporophytic self-incompatibility in Senecio squalidus L. (Asteraceae) II: a spatial autocorrelation approach to determining mating behaviour in the presence of low S allele diversity. - Brennan, A; Harris, S; Hiscock, S (2003)
We recently estimated that as few as six S alleles represent the extent of S locus diversity in a British population of the self-incompatible (SI) coloniser Senecio squalidus (Oxford Ragwort). Despite the predicted constraints to mating imposed by such a low number of S alleles, S. squalidus maintains a strong sporophytic self-incompatibility (SSI) system and there is no evidence for a breakdown of SSI or any obvious negative reproductive consequences for this highly successful coloniser. The present paper assesses mating behaviour in an Oxford S. squalidus population through observations of its effect on spatial patterns of genetic diversity and thus the extent to which it is responsible for ameliorating the potentially detrimental reproductive consequences of low S allele diversity in British S. squalidus. A spatial autocorrelation (SA) treatment of S locus and allozyme polymorphism data for four loci indicates that mating events regularly occur at all the distance classes examined from 60 to 480 m throughout the entire sample population. Less SA is observed for S locus data than for allozyme data in accordance with the hypothesis that SSI and low diversity at the S locus are driving these large-scale mating events. The limited population structure at small distances of 60 m and less observed for SA analysis of the Me-2 locus and by F-statistics for all the allozyme data, is evidence of some local relatedness due to limited seed and pollen dispersal in S. squalidus. However, the overall impression of mating dynamics in this S. squalidus population is that of ample potential mating opportunities with many individuals at large population scales, indicating that reproductive success is not seriously affected by few S alleles available for mating interactions.